Prospects of acne vaccines targeting secreted virulence factors of Cutibacterium acnes - Sunita Keshari; Manish Kumar; Arun Balasubramaniam; Ting-Wei Chang; Yun Tong; Chun-Ming Huang (Taylor & Francis Group, 2019)
Introduction: Acne vulgaris afflicts many people, and despite the multitude of the anti-acne products on the market, there is still no effective treatment that can prevent and cure this disease. The severity of acne vulgaris is highly associated with the inflammatory response to Propionibacterium acnes (P. acnes) now referred to as Cutibacterium acnes (C. acnes), an opportunistic skin bacterium in the human skin microbiome. Areas covered: We here provide the prospects of creating acne vaccines targeting secreted virulence factors of C. acnes including secretory Christie-Atkins-Munch-Peterson (CAMP) factor. Neutralization of secreted virulence factors by either active or passive vaccination may have a lower risk of disturbing the microbial ecosystem in the human skin microbiome. Expert opinion: Major steps could be taken to start a public vaccination program at an early age to prevent the future occurrence of acne vulgaris. Future therapeutic monoclonal antibodies can be designed to specifically neutralize virulence factors of C. acnes including CAMP factors without disrupting the optimal balance of C. acnes in the human skin microbiome and lowering the risk of creating drug-resistant C. acnes. Targeting secreted virulence factors without disturbing the commensal relationship of host can be a novel gateway towards the therapeutic treatment of acne vulgaris.